2003
DOI: 10.1093/aob/mcg040
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soybean to Oxygen Deficiency and Elevated Root-zone Carbon Dioxide Concentration

Abstract: Root flooding is damaging to the growth of crop plants such as soybean (Glycine max L.). Field flooding for 3 d often results in leaf chlorosis, defoliation, cessation of growth and plant death. These effects have been widely attributed solely to a lack of oxygen in the root-zone. However, an additional damaging factor may be CO(2), which attains levels of 30 % (v/v) of total dissolved gases. Accordingly, the effects of root-zone CO(2) on oxygen-deficient soybean plants were investigated in hydroponic culture.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
96
1
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 31 publications
7
96
1
11
Order By: Relevance
“…Em períodos de maior umidade, os solos compactados, por possuírem menor quantidade e continuidade de poros, podem apresentar deficiência de oxigênio para as raízes das plantas (Lapen et al, 2004). Além da falta de oxigênio (Drew, 1983), o aumento na concentração de CO 2 no ambiente radicular afeta as plantas (Boru et al, 2003;Greenway et al, 2006 . Essa camada limitante, ocasionada pela compactação, também apareceu na área escarificada, o que pode ser atribuído à dificuldade de coleta de amostras com estrutura preservada em condições de solo mobilizado; isso normalmente induz a coleta nas zonas menos alteradas, as quais não sofreram desestruturação pela haste do escarificador devido à sua alta resistência ou compactação e, dessa forma, isso se reflete em maior densidade.…”
Section: Resultsunclassified
“…Em períodos de maior umidade, os solos compactados, por possuírem menor quantidade e continuidade de poros, podem apresentar deficiência de oxigênio para as raízes das plantas (Lapen et al, 2004). Além da falta de oxigênio (Drew, 1983), o aumento na concentração de CO 2 no ambiente radicular afeta as plantas (Boru et al, 2003;Greenway et al, 2006 . Essa camada limitante, ocasionada pela compactação, também apareceu na área escarificada, o que pode ser atribuído à dificuldade de coleta de amostras com estrutura preservada em condições de solo mobilizado; isso normalmente induz a coleta nas zonas menos alteradas, as quais não sofreram desestruturação pela haste do escarificador devido à sua alta resistência ou compactação e, dessa forma, isso se reflete em maior densidade.…”
Section: Resultsunclassified
“…Some researchers have indicated that high carbon dioxide levels [30] [31] [32] or impaired mineral diffusion [33] in the rhizosphere are key factors influencing crop waterlogging injury. Additionally, low partial pressure of oxygen around the roots [17] [34] should be considered an important factor in the development of waterlogging injury in soybean plants.…”
Section: Analysis Of the Mechanism Underlying Field Waterlogging Tolementioning
confidence: 99%
“…습해는 주로 뿌리에서 나타나며, 수분 과잉이 지속됨에 따라 뿌리에서 산소부족과 환원성 유해물질 등이 집적되고 (Park et al, 1999), 이것이 뿌리의 호흡을 저해하여 수분이나 양분의 흡수 및 이동을 억제하고 결국 양분 부족 등의 이유로 작물 체의 생장량이 감소된다 (Boru et al, 2003). 였다 .…”
unclassified